Obsessive‐Compulsive Disorder: The Process of Parental Adaptation and Implications for Genetic Counseling. Issue 5 (7th December 2015) - Andrighetti, Heather; Semaka, Alicia; Stewart, S. Evelyn; Shuman, Cheryl; Hayeems, Robin; Austin, Jehannine
Abstract: Obsessive‐compulsive disorder (OCD) has primarily pediatric onset and well‐documented unique impacts on family functioning. Limited research has assessed the understanding that parents of children with OCD have of the etiology of the condition, and there are no data regarding potential applications of genetic counseling for this population. We recruited 13 parents of 13 children diagnosed with OCD from the OCD Registry at British Columbia Children's Hospital, and conducted qualitative semi‐structured telephone interviews to explore participants' experiences with their child's OCD, causal attributions of OCD, and perceptions of two genetic counseling vignettes. Interviews were audio‐recorded, transcribed, and analyzed using elements of grounded theory qualitative methodology. Analysis revealed key components and contextual elements of the process through which parents adapt to their child's OCD. This adaptation process involved conceptualizing the meaning of OCD, navigating its impact on family dynamics, and developing effective illness management strategies. Adaptation took place against a backdrop of stigmatization and was shaped by participants' family history of mental illness and their child's specific manifestations of OCD. Parents perceived genetic counseling, as described in the vignettes, as being empowering, alleviating guilt and blame, and positively impacting treatment orientation. These data provide insight into the process of parental adaptation to pediatric OCD, and suggest that genetic counseling services for families affected by OCD may help facilitate adaptation to this illness.